RAGAM TEKNIK DAN BAHAN KERAJINAN TANGAN SEBAGAI SUMBER BELAJAR SENI BUDAYA DAN PRAKARYA SEKOLAH DASAR - Sumanto; Muhana Gipayana; Rumidjan (Universitas Negeri Malang, 2017)
Abstract: The study aims at describing a variety of handicraft techniques and materials which exist in Malang. This study employed qualitative descriptive approach. The subject of this study was handicraft home industry in Malang. The data collection of this study obtained by conducting observation, documentation, and interviews. The results indicated that (1) home industry of handicraft in Malang is feasible to be utilized as a learning resource in elementary school. In addition, the variety of technique of making handicrafts noted within this study are wickerworking, carving, sewing, tie, stringing-beading, application, embroidering, batik, folding, clay crafting, spinning, rotating, printing, screen printing, painting, scratching and lathing. (2) The variety of handicrafts materials selected or used is in the form of natural and artificial materials such as clay, katu, corn husk, cloth, plastic, and paper. Abstrak: Penelitian bertujuan mendeskripsikan: ragam teknik, dan bahan kerajinan tangan di Kota Malang. Pendekatan deskriptif kualitatif. Subyek home industri kerajinan tangan di Malang. Pengumpulan data: observasi, dokumentasi dan wawancara. Hasil: (1) pada produk home industri kerajinan tangan yang ada di Kota Malang dapat dipelajari sebagai sumber belajar di SD. Ragam teknik atau cara pembuatan yaitu anyaman, ukir, jahit, ikat, merangkai-meronce, aplikasi, menyulam, membatik, melipat, membutsir, pilin, putar, mencetak, sablon, melukis, menoreh danbubut. (2) ragambahan kerajinan tangan yang dipilih atau digunakan yaitu berupa bahan alam dan bahan buatan contohnya tanah liat, katu, klobot jagung, kain, platik, dan kertas. Kata Kunci: teknik, bahan kerajinan tangan, sumber belajar, seni budaya, SD